The Status of Actual Costs in Billing Rescheduling: Perspectives of Fiqh Muamalah and Regulation of Islamic Financial Institutions (IFI) Post DSN-MUI Fatwa No. 134 of 2020 - Muhammad Irkham Firdaus*; Robbie Azrial Akbar Z.; Fika Hidayatulloh (AL-IKTISAB: Journal of Islamic Economic Law, 2025)
The practice of rescheduling murabahah financing is a crucial mechanism within Islamic Financial Institutions (IFI) to address non-performing financing and simultaneously adhere to the principle of prudence, as mandated by the Islamic Banking Law. IFI are obligated to comply with the sharia provisions established by the National Sharia Council (DSN) of the Indonesian Ulama Council (MUI). This research specifically aims to examine the status and implications of DSN-MUI Fatwa No. 134 of 2020 concerning Actual Costs Due to Billing Rescheduling within the framework of Islamic law and financial regulation in Indonesia. This research employs a qualitative library research method with a content analysis technique. Data is gathered from fiqh muamalah literature, DSN-MUI fatwa, and the regulations of the Financial Services Authority (OJK) and the Islamic Banking Law. The analysis reveals a significant intersection between the perspective of fiqh muamalah and IFI Regulation following DSN-MUI Fatwa No. 134 of 2020. From the fiqh muamalah side, the fatwa strictly prohibits increasing the principal debt to avoid riba. However, the recognition of imposing actual costs triggers contemporary fiqh debate, the majority scholarly view tends to reject any cost addition on debt unless it is purely allocated as a social fund (ta'zir). This raises substantial questions regarding the status of actual costs if they are recognized as operational revenue for the IFI. From the IFI Regulation side, DSN-MUI Fatwa No. 134 of 2020 holds a very strong position as a legally binding compliance standard, mandated by the Islamic Banking Law. The fatwa serves a dual function, as sharia legitimacy for prudent rescheduling practices, and as a tool for consumer protection against fictitious costs.